Synthesis, Characterization, and Cytotoxicity of Iron Oxide Nanoparticles. (22nd December 2013) - Kanagesan, S.; Hashim, M.; Tamilselvan, S.; Alitheen, N. B.; Ismail, I.; Hajalilou, A.; Ahsanul, K.
Abstract : In order to study the response of human breast cancer cells' exposure to nanoparticle, iron oxide ( α -Fe2 O3 ) nanoparticles were synthesized by a simple low temperature combustion method using Fe(NO3 )3 ·9H2 O as raw material. X-ray diffraction studies confirmed that the resultant powders are pure α -Fe2 O3 . Transmission electron microscopy study revealed the spherical shape of the primary particles, and the size of the iron oxide nanoparticles is in the range of 19 nm. The magnetic hysteresis loops demonstrated that the sample exposed ferromagnetic behaviors with a relatively low coercivity. The cytotoxicity of α -Fe2 O3 nanoparticle was also evaluated on human breast cancer cells to address the current deficient knowledge of cellular response to nanoparticle exposure.